Behavioural Consequences of Frontal Cortex Grafts and Enriched Environments after Sensorimotor Cortex Lesions. (1995) - Christie, Michael A.; Dalrymple-Alford, John C.
Abstract : Past studies have experienced difficulty in achieving graft survival and behavioural recovery after sensorimotor cortex lesions. In the present work, adult female rats trained preoperatively to cross a narrow beam for food reward were maintained in standard group cages or an enriched environment, commencing one week after a unilateral lesion. One month post-lesion, half of these rats received multiple suspension grafts of (E20) fetal frontal cortex, placed adjacent to the lesion cavity, and 8 days later recovery of beam-walking skills was examined for a six-week period. The grafts survived in all cases with an appropriate lesion, a notable result given the one month lesion-graft delay, but graft volume was not influenced by postoperative environment. The substantial lesion-induced deficits evident just prior to differential housing showed a marked reduction by the start of post-graft testing, but relative to intact controls a persistent deficit in foot slip errors occurred in all lesion groups. Irrespective of graft status, postoperative enrichment prevented the occurrence of severe foot slips, especially early in retraining. The frontal grafts, however, enhanced beam-walking recovery by reducing the overall frequency of foot slips on early post-grafting sessions, an effect we suggest is related to graft-derived trophic influences, but this measure was not significantly improved by postoperative enrichment.